Теплоотдача при кипении. Т.1 ( библиографический указатель литературы 1950 - 1973 гг. ) - Гурович Б. М.; Тактаева Л. Н.; Сотникова Т. В.; Мурадъян В. С.; Мансурова Л. Ф. (Ташкент, [Б. и.], 1974)
Исключено из фонда НТБ ТПУ